(3eOGQc GdCMcGes - (3GdehShj GdYGedj GdLHYj, eMeO Hf Ydj Hf MSjf GdehShj GdYGedj, J (B1009(3g` (B1600(3es
(3ChdgG (B:s
(3ChdgG(B: (3hGdeO dG GdEYQGH hjYQa chf GdecJhH bQBfG Hchfg dG jMJed EdG Pdc hEf GfJai GdCeQGf adG JMQje hGdeQGO HGdeS GdedGbGJ jLRA ef GdHTQI haj GdXaQ hGdTYQs
(3BNQgG (B:s
(3BNQgG(B: (3GdeQGO HGdJaQjb GYJcGa jhe ef jhe ef GdYgO Ke GdKGdK Yf GdfPQ hgcPG, haj Med GdYHGOI Ydjg HYO Cf cGf GdCXgQ (B... (3dGfJaGA GdeGfY efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 507s
(3GdPQjYI, L (B20: 158s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis